2016
DOI: 10.1038/nrdp.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic human papillomavirus infection

Abstract: Infections with human papillomavirus (HPV) are common and transmitted by direct contact. Although the great majority of infections resolve within 2 years, 13 phylogenetically related, sexually transmitted HPV genotypes, notably HPV16, cause - if not controlled immunologically or by screening - virtually all cervical cancers worldwide, a large fraction of other anogenital cancers and an increasing proportion of oropharyngeal cancers. The carcinogenicity of these HPV types results primarily from the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
656
1
46

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 716 publications
(769 citation statements)
references
References 202 publications
6
656
1
46
Order By: Relevance
“…The most important HPV‐induced malignancy is cervical cancer, which is the fourth most common cancer in women worldwide 6. The vast majority of cervical cancer is caused by HPV16 and HPV18 (60 and 15% of cases, respectively) 6, 7. The likelihood to get infected with a high‐risk HPV type and consequently develop cancer was reduced after prophylactic vaccines became available for immunization of adolescents in 2006 8.…”
Section: Introductionmentioning
confidence: 99%
“…The most important HPV‐induced malignancy is cervical cancer, which is the fourth most common cancer in women worldwide 6. The vast majority of cervical cancer is caused by HPV16 and HPV18 (60 and 15% of cases, respectively) 6, 7. The likelihood to get infected with a high‐risk HPV type and consequently develop cancer was reduced after prophylactic vaccines became available for immunization of adolescents in 2006 8.…”
Section: Introductionmentioning
confidence: 99%
“…Despite widespread screening programs, cervical cancer remains frequent cancer among women worldwide, with the highest mortality rates in developing countries 1. Although human papillomavirus (HPV) vaccines are available, cervical cancer still causes a considerable amount of death because of the limited application of the vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…The focus is on HPV16, the most frequent and most carcinogenic type,12, 13 which is also the most difficult to control by vaccination8 due to its special propensity to persist. In a previous study,14 using idealized sexual contact structures, we have shown how HPV control through vaccination becomes more challenging in a population transitioning from a traditional to a gender‐equal sexual behavior.…”
Section: Introductionmentioning
confidence: 99%